2022
DOI: 10.9770/jesi.2022.10.1(19)
|View full text |Cite
|
Sign up to set email alerts
|

Impact of selected factors on digitalization of financial sector

Abstract: The financial sector is introducing new services to meet consumer needs at a time of information society and rapid technological awareness growth. The study aims to summarize the existing global trends in banking sector digitalization and informatization and assess the impact of selected macroeconomic indicators on them. The World Bank's data were used for the principal analysis. We offer a novel model for evaluating relationships between banking digitalization and macroeconomic processes based on theoreticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Summarizing the green competitiveness concept, studied recently by (Cheng et al, 2019); (Cheng et al, 2018); (Fu et al, 2017a); (Tsai et al, 2015); (Duffett et al, 2018); (Fu et al, 2017b), (Lin & Chen, 2017); (Mishra, n.d.); (Konuk et al, 2015); (Mwesigwa Banya & Biekpe, n.d.); (Wang et al, 2016); (Barysienė et al, 2015); (Khvesyk et al, 2018), (Barysienė et al, 2015); (Maitre et al, 2018); (Khalatur et al, 2022). It was found that the majority of researchers are looking into different aspects of green competitiveness, such as energy consumption and energy-saving competitiveness (16.66%), infrastructure, construction, and innovation competitiveness (16.66%), ecological environment competitiveness related to environmental protection (33.33%), economic and social sustainable competitiveness (33.33%), natural resource competitiveness (16.66%), and employees' skills and human resource competitiveness (14.66%).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Summarizing the green competitiveness concept, studied recently by (Cheng et al, 2019); (Cheng et al, 2018); (Fu et al, 2017a); (Tsai et al, 2015); (Duffett et al, 2018); (Fu et al, 2017b), (Lin & Chen, 2017); (Mishra, n.d.); (Konuk et al, 2015); (Mwesigwa Banya & Biekpe, n.d.); (Wang et al, 2016); (Barysienė et al, 2015); (Khvesyk et al, 2018), (Barysienė et al, 2015); (Maitre et al, 2018); (Khalatur et al, 2022). It was found that the majority of researchers are looking into different aspects of green competitiveness, such as energy consumption and energy-saving competitiveness (16.66%), infrastructure, construction, and innovation competitiveness (16.66%), ecological environment competitiveness related to environmental protection (33.33%), economic and social sustainable competitiveness (33.33%), natural resource competitiveness (16.66%), and employees' skills and human resource competitiveness (14.66%).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Other studies discussing the issue of banking digitalization acknowledge that new technologies will also further improve the quality of services and intensify the growth in the banking sector, as well as the economic growth of the country [3,4]. Banking automation and digitalization will continue due to ongoing innovation in the banking system and Systems 2023, 11, 534 2 of 28 also due to pressure from adjacent industries competing with the banking system in various segments.…”
Section: Introductionmentioning
confidence: 99%
“…It is hypothesized that regions or nations with advanced levels of digitalization will witness improved economic outcomes, including heightened GDP growth and augmented production. Understanding the dynamics of global economic growth with respect to the digitization of the financial sector is crucial [3]. Enhancing financial accessibility has a positive impact on economic growth, while simply having greater access to banking services does not necessarily spur economic growth [40].…”
mentioning
confidence: 99%